Exogeneus Force Theory, Sebuah Antitesis Teori Negara Otonom Dalam Formulasi Kebijakan Publik Perubahan Iklim Di Kota Palangka Raya - Ferry Setiawan; Ahmad Saefulloh; Reny Puspita Syari Nasution (Administratio, 2023)
Autonomous state theory is a view to see how public policy is implemented. Even if a policy is unable to overcome economic problems because it is not tied to the provision of public goods, the state still has the power to make its own policies. From the perspective of social goals to avoid damage, climate change and disaster adaptation policies in Indonesia are examples of appropriate policies that can be developed using this. This research aims to analyze whether the Autonomous State Theory can be reapplied to the emergence of climate change adaptation policies in the city of Palangka Raya or whether exogenous incentives have more influence on the implementation of climate change policies or not. In this research, the author used qualitative methods. Conducting an in-depth case study on the implementation of climate change policies in the City of Palangka Raya. This may involve interviews with policy makers, stakeholders, and analysis of policy documents. In-depth interviews were conducted with various parties involved in the climate change policy formulation process, namely, government, academics, environmental activists and other stakeholders. In addition, Analyze policy documents, reports and other information resources to understand the context, objectives and impact of climate change policies in the City of Palangka Raya. The data sources for this research are generally primary and secondary data. To be able to answer this research question, analysis techniques using qualitative methods are needed. The results of the research conclude that the exogenous theory is the antithesis of the Autonomous State Theory in formulating public policy regarding climate change in the city of Palangka Raya. This theory emphasizes the importance of involving actors other than the state in reducing the impacts of climate change. Countries must work together with private companies, international organizations, and civil society to develop effective solutions.